The impact of biomass withdrawal strategy on the biomass selection and polyhydroxyalkanoates accumulation of mixed microbial cultures - Cruz, Rafaela A. P. (2022)
UIDP/04378/2020 UIDB/04378/2020 LA/P/0140/2020 SFRH/BD/110673/2015